The impact of entering poverty on the unmet medical needs of Korean adults: a 5-year cohort study - Yun Hwa Jung; Sung Hoon Jeong; Eun-Cheol Park; Sung-In Jang (BMC Public Health, 2022)
Abstract Background Studies on the effects of poverty on unmet medical needs are limited. Therefore, this study aimed to identify the impact of entering poverty on the unmet medical needs of South Korean adults. Methods This study used data from the Korea Health Panel Survey (2014–2018) and included 10,644 adults. Logistic regression was used to examine the impact of entering poverty on unmet medical needs (poverty status: no → no, yes → no, no → yes, yes → yes; unmet medical needs: no, yes). Poverty line was considered to be below 50% of the median income. Results When entering poverty, the proportion of unmet medical needs was 22.8% (adjusted odds ratio [AOR] 1.17, 95% confidence interval [CI] 1.01–1.36). Men (AOR 1.29, 95% CI 1.02–1.64), rural dwellers (AOR 1.24, 95% CI 1.01–1.50), and national health insurance (NHI) beneficiaries (AOR 1.21, 95% CI 1.04–1.42) were susceptible to unmet medical needs and entering poverty. Poverty line with below-median 40% had an AOR of 1.48 (95% CI 1.28–1.71). For the cause of unmet medical needs, the AORs were 1.50 for poverty (95% CI 1.16–1.94) and 1.08 for low accessibility to health care and information (95% CI 0.79–1.48). Conclusions Entering poverty had the potential to adversely affect unmet medical needs. Men, rural dwellers, and NHI beneficiaries were vulnerable to unmet medical needs after entering poverty. Rigid definitions of poverty and inaccessibility to health care and information increase the likelihood of unmet medical needs and poverty. Society must alleviate unmet medical needs due to the increase in the population entering poverty.